AN UNUSUAL RECTAL FOREIGN BODY: SUCCESSFULLY REMOVED BY USING A FOLEY CATHETER - Seyed Mostafa Shiryazdi; Latife Jabbari (Gomal Journal of Medical Sciences, 2016)
Foreign bodies in the rectum is a well described phenomenon that most commonly seen in association with anal eroticism. Patients may be admitted only with rectal pain or bleeding without any history of rectal insertion. We describe a single 25 years-old man with a rectal foreign body at 20cm of anal wedge which presented only as a rectal bleeding with constipation. Foley catheter number 20 was passed through the anal canal behind the foreign body and the balloon was inflated. After firmly traction, anal dilatation was done and the foreign body was safely extracted with the aid of ring forceps through the anus without any complications.